2020
DOI: 10.1088/2057-1976/abb5e9
|View full text |Cite
|
Sign up to set email alerts
|

The sequential effects of a multifactorial detergent based decellularization process on bovine pericardium

Abstract: Decellularization is a promising method for obtaining extracellular matrix scaffolds (ECM) to be used as replacement material in reconstructive procedures. The effectiveness of decellularization and the alterations to the ECM vary, depending on several factors, including the tissue source, composition and density. With an optimized decellularization process, decellularized scaffolds can preserve the spatial and temporal ECM microenvironment, which play an integral role in modulating cell migration, proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…ECM proteins are conserved among different species and can serve as a scaffold promoting host tissue regeneration through cell attachment, migration, and proliferation [ 43 ]. In a subsequent study, the decellularization technique used in this study was also shown to remove lipids [ 30 ], which can further contribute to decreasing the calcification potential of the tissue [ 44 ]. In another study by our group, the decellularized bovine pericardium, processed using this proprietary method, was implanted into the main pulmonary artery and the descending aorta of juvenile sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECM proteins are conserved among different species and can serve as a scaffold promoting host tissue regeneration through cell attachment, migration, and proliferation [ 43 ]. In a subsequent study, the decellularization technique used in this study was also shown to remove lipids [ 30 ], which can further contribute to decreasing the calcification potential of the tissue [ 44 ]. In another study by our group, the decellularized bovine pericardium, processed using this proprietary method, was implanted into the main pulmonary artery and the descending aorta of juvenile sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The SDS and Triton-X100 group and SDS, TritonX-100 and ammonium group had better cytobiocompatibility, with the porosity structure maintained in all groups [ 47 ]. The addition of ammonium might have the added benefit of retaining the glycosaminoglycan content (GAGs) [ 48 ], which was found to significantly decreased in bovine pericardium processed using our proprietarary multi-detergent based decellularization process [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decellularization can be obtained through various methods (physical, enzymatic, or chemical) but needs to be tailored for each tissue type depending on cellularity, density, lipid content, and thickness ( 75 ). Each step of the process has different effects on the outcome ( 36 ), and related techniques may yield different results depending on small variations in the technique. Our decellularization methodology has been developed over various iterations, and the results reported here are from tissues with encouraging performance in the subcutaneous rat model and aortic and pulmonary artery ovine implants ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…These processes can be broadly divided into decellularization, fixation, and detoxification. After evaluating the contributions of various decellularization steps and combinations, we have developed a unique method to decellularize bovine pericardium (BP) without significantly altering its strength and collagen structure ( 36 , 37 ). This decellularized (DE) tissue performed well in 6-month implants in ovine aortas and pulmonary arteries, with less pannus formation, limited calcification, and adequate strength ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the decellularization protocol they used reduced the GAG content, with resultant increased extensibility and changes in the relaxation behavior of the pulmonary valve leaflets [ 44 ]. The method currently used led to a reduction of the GAG content when used for the decellularization of bovine pericardium [ 48 ]. The GAG content was not evaluated in the current study, and the effect of this decellularization method on the GAG content of the pulmonary homografts should be investigated.…”
Section: Discussionmentioning
confidence: 99%